PO.7.142 Health-related quality of life across the spectrum of connective tissue diseases: a latent profile analysis. (27th September 2022) - Dyball, S; Reynolds, J; Bruce, IN; Parker, B
Abstract : Purpose: Poor health-related quality of life (HR-QoL) is well recognised within patients with connective tissue diseases (CTD). We hypothesised that subgroups of patients across the spectrum of CTD experience different HR-QoL patterns, and aimed to determine patient-level characteristics associated with subgroup membership. Methods: The medical outcomes short-form 36 (SF-36) questionnaire was used, and the eight continuous domains of the SF-36 questionnaire were derived which range from 0 to 100, with higher scores reflecting better HR-QoL. We used the 'mclust 5.4.9' model-based clustering package in R V4.0.4 to identify latent profiles (LP) of patients who experienced distinct HR-QoL patterns. Variances were equated and covariances fixed to zero. Missing values were imputed using methodology suggested by the SF-36 manual. Number of comorbidities included osteoarthritis, chronic kidney disease, ischaemic heart disease, cancer, diabetes, reflux disease, chronic liver disease, obstructive airway disease or interstitial lung disease, thyroid disease, stroke, vitiligo, Addison's disease and atrial fibrillation. Multivariable ordinal logistic regression was used to determine patient-level characteristics associated with membership in the HR-QoL subgroups. Models were adjusted for ethnicity, sicca, fibromyalgia, and number of co-morbidities. Results: 309 patients with a variety of CTDs recruited into LEAP completed the SF-36 questionnaire, (280 [90.6%] women, mean [SD] age 48.9 [12.9] years). There were 115 (37.2%) patients with lupus, 72 (23.3%) undifferentiated CTD, 56 (18.1%) primary Sjögren's syndrome and 66 (21.4%) patients with systemic sclerosis, idiopathic inflammatory myopathy or an overlap syndrome (SSc-IIM). Three LP were identified with poor (n=89), average (n=190) and excellent (n=30) HR-QoL ( figure 1 ). In multivariable models, LP were not associated with diagnostic grouping (Sjogren's: OR 0.97 [95% CI 0.46–2.06]; undifferentiated CTD: OR 1.05 [95% CI 0.57–1.92]; SSc-IIM: OR 0.89 [95% CI 0.48–1.68]). Black ethnicity (OR 0.26 [95% CI 0.10–0.70]) or Asian ethnicity (OR 0.41 [95% CI 0.21–0.81]), concomitant fibromyalgia (OR 0.44 [95% CI 0.22–0.86]), sicca phenomenon (OR 0.56 [95% CI 0.35–0.91]) and multi-morbidity (OR 0.80 [95% CI 0.63–1.00]) were associated with membership of a lower HR-QoL LP. Conclusion: CTD patients can be clustered into distinct HR-QoL subgroups agnostic of their clinical diagnosis which may have meaningful implications in practice for stratifying therapy. This study highlights that sicca syndrome, ethnicity, fibromyalgia and multi-morbidity are key areas to focus on in improving HR-QoL in patients with a CTD, irrespective of clinical diagnosis or antibody profile.